The Influence of PBL-Based Worksheets on Interest and Learning Outcomes - sari, Tri wulan; Muhammad Iqbal Filayani (Bioeduca : Journal of Biology Education, 2024)
This research is motivated by students' difficulty understanding the material taught, the tendency of learning processes to be boring, and the continued use of conventional teaching materials. This study aims to determine the influence of using PBL-based worksheets on students' interests and learning outcomes. This research is quantitative in nature with a quasi-experimental design. Data collection methods in this study include questionnaires, tests, and documentation. Subject matter experts and media experts conducted the validity test. The data analysis technique used is quantitative descriptive analysis. The results show a significant positive influence between using PBL-based worksheets and interest and learning outcomes. This is based on the results of MANOVA tests using questionnaire results and N-Gain values, which obtained a Sig. (2-tailed) value of 0.000, indicating the influence of using PBL-based worksheets on interest and learning outcomes.